Kebijakan Bahasa dalam Lanskap Linguistik di Era Super-Diversity: Bahasa Asing (Bahasa Inggris) di Ruang Publik - Riandi Riandi; Hayati Nupus (Universitas Mathla'ul Anwar Banten, 2022)
This conceptual paper presents a literature review of language landscape studies on the interaction of multilingualism, multiculturalism, and globalization in the reality of English learning education (ESL). Language has a great influence on human life through the forms of expression it conveys. Likewise in the social life of the wider community in general. In addition, language also plays an important role. In addition, the central government has rules and guidelines that affect local governments. The same applies to government language policies. Language policy is followed by language planning, which leads to social change. The areas of language policy include education, economics, politics, regional languages ​​and literature, and law. All of that is inseparable from the language policies regulated by the governments of each country or region that use the language environment in the public sphere. Therefore, English cannot be used without another language, although it is subject to national and regional language policies. As a result, the use of English in public places requires the use of language equivalents in multilingual public forms, both in historical and cultural contexts, such as signage. However, because the unit of analysis in the linguistic landscape is the symbol, it provides the linguistic context of a particular region (roads, villages, buildings, countries, and environments), the linguistic landscape in this social conception, or the diversity of populations. English cannot be the only language used to represent signs. In the public sphere, taking into account the rise of bilingualism, the dominance of the national language, and a common language policy. However, the diversity of English is still growing. In short, English as used in this study of the linguistic landscape in the public sphere is a contradiction between language practice and language policy, and public understanding. Keywords: Language Policy, Linguistic Landscape, Era of Super Diversity, Foreign Languages (English).